Nanowire Junction Induced High Threshold Voltage in Poly(3‐hexylthiophene) Mesoscale Crystalline Thin‐Film Transistors with Significantly Enhanced Mobility. Issue 4 (28th January 2020) - Deng, Yadan; Jiang, Jingzan; Sun, Jun; Hu, Yufeng; Cui, Qiuhong; Deng, Zhenbo; Lou, Zhidong; Hou, Yanbing; Teng, Feng
Abstract : Fabrication of nanowires in polymer films can dramatically enhance the mobility of thin‐film transistors (TFTs). Unlike the popular method of forming nanowires after spin‐coating films, here a water‐bath method to fabricate the micrometer‐long nanowires in the poly(3‐hexylthiophene) (P3HT) solution is introduced, which is suitable for large‐area printing electronic application. The resulting transistor exhibits significantly enhanced mobility and excellent device stability. However, the threshold voltage of the device is increased, compared with the amorphous film device. The underlying mechanism of the mesoscale crystalline induced threshold voltage increase has been rarely studied. The temperature‐dependent characteristics imply that the activation energy of the device with nanowires is higher than that of the amorphous one, indicating nanowires can introduce deep traps. This suggests that the charge transport is mainly limited by the deep traps at the junctions between the nanowires considering the trap density inside the nanowires is significantly low. The deep traps introduced by the junctions can increase the threshold voltage as the device needs higher voltage to fill these traps in the channel before the device is turned on. This explains why the devices with nanowires have an increased threshold voltage while their mobilities are dramatically enhanced. Abstract : A high‐mobility poly(3‐hexylthiophene) (P3HT) thin‐film transistor is demonstrated by preparing the nanowire‐contained polymer solution via a water‐bath method. The mobility of the devices with nanowires is 60 times higher than that of the amorphous devices. The origin of the relative high‐threshold voltage in such mesoscale crystalline devices is identified as the deep traps at the junction.